Knockout mouse models as a resource for the study of rare diseases - Patricia da Silva-Buttkus; Nadine Spielmann; Tanja Klein-Rodewald; Christine Schütt; Antonio Aguilar-Pimentel; Oana V. Amarie; Lore Becker; Julia Calzada-Wack; Lillian Garrett; Raffaele Gerlini; Markus Kraiger; Stefanie Leuchtenberger; et al. (Mammalian Genome, 2023)
Rare diseases (RDs) are a challenge for medicine due to their heterogeneous clinical manifestations and low prevalence. There is a lack of specific treatments and only a few hundred of the approximately 7,000 RDs have an approved regime. Rapid technological development in genome sequencing enables the mass identification of potential candidates that in their mutated form could trigger diseases but are often not confirmed to be causal. Knockout (KO) mouse models are essential to understand the causality of genes by allowing highly standardized research into the pathogenesis of diseases. The German Mouse Clinic (GMC) is one of the pioneers in mouse research and successfully uses (preclinical) data obtained from single-gene KO mutants for research into monogenic RDs. As part of the International Mouse Phenotyping Consortium (IMPC) and INFRAFRONTIER, the pan-European consortium for modeling human diseases, the GMC expands these preclinical data toward global collaborative approaches with researchers, clinicians, and patient groups. Here, we highlight proprietary genes that when deleted mimic clinical phenotypes associated with known RD targets ( Nacc1, Bach2, Klotho alpha ). We focus on recognized RD genes with no pre-existing KO mouse models ( Kansl1l, Acsf3, Pcdhgb2, Rabgap1, Cox7a2 ) which highlight novel phenotypes capable of optimizing clinical diagnosis. In addition, we present genes with intriguing phenotypic data ( Zdhhc5, Wsb2 ) that are not presently associated with known human RDs. This report provides comprehensive evidence for genes that when deleted cause differences in the KO mouse across multiple organs, providing a huge translational potential for further understanding monogenic RDs and their clinical spectrum. Genetic KO studies in mice are valuable to further explore the underlying physiological mechanisms and their overall therapeutic potential.